Electrophoretic display comprising black, white, red, and yellow particles. Issue 5 (31st March 2022) - Zang, HongMei; Lin, Craig; Du, Hui; Gu, Haiyan; Parent, Mary; Chen, Yajuan; Liu, Lei
Abstract: A four‐particle electrophoretic display (EPD), Spectra™ 3100, was released in 2021. It targets electronic shelf label applications and signage applications by providing four primary optical states of black, white, red, and yellow, as well as dithering capability to show graphic images. Specially engineered black, white, red, and yellow particles in the electrophoretic ink respond to different electric fields to show pigment intrinsic colors on the display. The imaging film produced from this technology can reach a typical contrast ratio of 30:1 while maintaining a maximum driving voltage of ±15 V. The vibrant red and yellow colors are ideal for highlighting. Consistent optical performances are achieved for all four optical states across the operating temperature range of 0°C to 40°C for a typical indoor environment. The electrophoretic ink is coated and sealed in a thin‐film Microcup® structure using an additive and high yield roll‐to‐roll manufacturing process to produce the imaging film. Active matrix (AM) module integration follows the conventional EPD module production process of lamination between the imaging film and thin‐film transistor (TFT) backplane. Abstract : A four‐particle electrophoretic display (EPD), Spectra™ 3100, provides four primary optical states of black, white, red, and yellow, as well as dithering capability to show graphic images. The imaging film produced from this technology can reach a typical contrast ratio of 30:1 while maintaining a maximum driving voltage of ±15 V.